A nexus between fiscal policy and inflation: a case study of Indonesia using SVAR model (Public Sector Economics - submission site, 2023)
This paper investigates the dynamic effects of changes in three government spending components – public sector wages and purchase of goods and services, energy and other subsidies, and transfers to households – on inflation and private consumption in Indonesia from 2001:Q1 to 2022:Q4, using non-recursive structural VAR model. The model consists of eight endogenous variables: exchange rate, output gap, tax ratio, government spending, inflation, debt ratio, interest rate, and private consumption. Structural decompositions reveal that inflation responses differ across three government spending components. Shocks to government subsidies are more likely to lead to higher inflation than shocks to other components. But even spending on subsidies does not always have a statistically significant effect on inflation. Surprisingly, government spending shocks – aggregate or by components – do not seem to have statistically significant impact on private consumption. The main effect of fiscal expansions may thus be a deterioration in public finances.